Helicobacter pylori and Uveitis: A Brief Narrative Literature Review - Markov, Gueorgui; Yani Zdravkov; Oscar, Alexander (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Helicobacter pylori (H. pylori) is a gram-negative bacterium that typically infects the mucosa of the stomach. H. pylori is the most frequent causative infectious agent of chronic gastritis and peptic ulcer disease. It has also been associated with a number of extra-gastric diseases-neurological, ocular, hematologic, cardiovascular, rheumatologic, metabolic, and allergic. The possible role of H. pylori in the pathogenesis of uveitis is still unclear. High H. pylori seroprevalence has been found in some studies in patients with other ocular diseases like blepharitis, central serous chorioretinopathy, ocular adnexal lymphoma, and glaucoma. Its seroprevalence in uveitis has been investigated in very few studies. In all of them, however, it was increased. Antibodies have also been found in the anterior chamber of patients with anterior uveitis. Besides, seropositivity was also increased in studies with hypertensive uveitis. Eradication of the bacterium has anecdotally led to the subsidence of anterior uveitis in one patient. In any case, a causal relationship, either infectious or autoimmune, cannot be made at this time due to the scarcity of available research on the problem.